2013
DOI: 10.1186/2193-1801-2-463
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis: are healthcare professionals missing an opportunity

Abstract: ObjectivesThe objective of the current study is to analyze different approaches of pharmacists and general practitioners towards availability and use of osteoporosis prescreening tools and to find out reasons that explain non utilization of such tools in clinical practice.SettingsAmong General practitioners and Community pharmacists in Pulau Penang, Malaysia.MethodologyAn explorative cross sectional study was carried out using convenience sampling approach. A pre-validated self- administered questionnaire was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Of the 10 GP survey respondents who reported using a screening tool, the FRAX was the most utilised screening tool, with 90% (n = 9) of GP survey respondents selecting this tool. This finding was similar to that seen in a study by Khan et al (2013) where FRAX was the most widely known screening tool among Malaysian GP survey respondents and pharmacists. However, it is important to note that the FRAX tool does not incorporate the number of fractures beyond one fracture, and the ability to add in all fractures would increase the risk profile (Compston et al, 2017).…”
Section: Wellington Gp Osteoporosis Assessment -Screening Toolssupporting
confidence: 90%
See 2 more Smart Citations
“…Of the 10 GP survey respondents who reported using a screening tool, the FRAX was the most utilised screening tool, with 90% (n = 9) of GP survey respondents selecting this tool. This finding was similar to that seen in a study by Khan et al (2013) where FRAX was the most widely known screening tool among Malaysian GP survey respondents and pharmacists. However, it is important to note that the FRAX tool does not incorporate the number of fractures beyond one fracture, and the ability to add in all fractures would increase the risk profile (Compston et al, 2017).…”
Section: Wellington Gp Osteoporosis Assessment -Screening Toolssupporting
confidence: 90%
“…the key studies identified by the researcher (Blazkova et al, 2010;Chami et al, 2006;Khan et al, 2013;Vytrisalova et al, 2014;Vytrisalova et al, 2017) this study's results should be relatable to future comparable studies. Statistical input and advice were sought regularly throughout this research undertaking.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Such women bear disruption in family relationship, social isolation, anxiety, embarrassment, fatigue, osteoporosis, bone fragility and sleep disturbance. 17,18 These symptoms should be addressed to improve the quality of life during periand post-menopausal phase. 6,19 There are several approaches to manage vasomotor symptoms during peri-menopausal and post-menopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Scavenging of free radicals by anti-oxidants reduced the process of liver cells fibrosis (Raja et al, 2006). Many plants have been identified as hepatoprotective like Trianthema decandra (Balamurugan and Muthusamy, 2008), Cocculus hirsutus (Thakare et al, 2009), Carica papaya (Sadeque and Begum, 2010), Carissa spinarum (Hegde and Joshi, 2010), Convolvulus arvensis (Ali et al, 2013), Dodonaea viscosa (Khan et al, 2013), Trichodesma sedgwickianum (Saboo et al, 2013), OfIpomoea staphylina (Bag and Mumtaz, 2013) and Khamira Gaozaban Ambri Jadwar Ood Saleeb Wala (Akhtar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%